Perception of students' motivations in gymnastic activities in physical education classes - Carla Vieira; Tatiana Rocha; António Manuel Azevedo (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Gymnastics encompasses a diverse spectrum of practices considered fundamental for students’ education process, promoting their physical, cognitive, social, and emotional development in an integrated manner. Nonetheless, its adoption in the school context falls short compared to other modalities.